(untitled) - Huguenin, John E. (Amsterdam ( The Netherlands ), 1989)
This book provides, in one place, basic information and considerations necessary to plan, build and operate seawater systems for culturing purposes. It provides design, construction and operations guidance for seawater (salinities from freshwater to brine) systems with flow rates of 10-1,000 gallons (40-4,000 liters) per minute.
Keywords: Mariculture,Marine aquariums, public; Equipment and supplies,Design and construction